2016
DOI: 10.1016/j.ajo.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Latanoprostene Bunod 0.024% and Timolol Maleate 0.5% in Open-Angle Glaucoma or Ocular Hypertension: The LUNAR Study

Abstract: LBN 0.024% QD in the evening was noninferior to timolol 0.5% BID over 3 months of treatment, with significantly greater IOP lowering in subjects with OAG or OHT at all but the earliest time point evaluated, and demonstrated a good safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 39 publications
0
83
0
7
Order By: Relevance
“…This radical affects an early step in the replication cycle of influenza viruses and NO has been shown to severely impair the replication of influenza A and B viruses 11. In the outflow physiology, NO has been reported to contribute to the physiological regulation of aqueous humor outflow and to lower intraocular pressure in various animal models and human patients 5, 12, 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…This radical affects an early step in the replication cycle of influenza viruses and NO has been shown to severely impair the replication of influenza A and B viruses 11. In the outflow physiology, NO has been reported to contribute to the physiological regulation of aqueous humor outflow and to lower intraocular pressure in various animal models and human patients 5, 12, 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…At the conclusion of the 3 month phase of the studies, pooled data from the studies showed significantly lower IOP in the LBN group compared with the timolol group at all time points (least squares mean IOP in the study eye ranged from 17.8 to 18.9 mmHg and from 19.0 to 19.7 mmHg, in the LBN 0.024% QD group and timolol 0.5% BID group, respectively) (Table ). Furthermore, the proportion of patients reaching an IOP of ≤18 mmHg was greater in the LBN group compared with the timolol group (Medeiros et al ., ; Weinreb et al ., ; Kaufman, ). Pooled results from the APOLLO and LUNAR open‐label safety extension phases demonstrated that the IOP reduction reached with LBN 0.024% was maintained up to 12 months, with no apparent loss of activity over time (Vittitow et al ., ).…”
Section: Pg Analogues As Ocular Hypotensive Agentsmentioning
confidence: 99%
“…The APOLLO (Weinreb et al ., ) and LUNAR (Medeiros et al ., ) studies were nearly identically designed phase 3 safety and efficacy studies of LBN 0.024% in patients with open‐angle glaucoma or ocular hypertension. Each study consisted of a 3 month active (timolol) comparator, double‐masked efficacy phase followed by a 9 month (APOLLO) or 3 month (LUNAR) open‐label safety extension (Table ).…”
Section: Pg Analogues As Ocular Hypotensive Agentsmentioning
confidence: 99%
“…Thus, in principle, the two different outflow pathways can be enhanced simultaneously. In phase 3 trials, a drug product containing 0.024% API dosed once a day was superior at all but one of the time points to the 0.5% timolol drug product dosed twice a day (Medeiros et al, ; Weinreb et al, ). The FDA approved this drug product, brand name Vyzulta™, in late 2017.…”
Section: Future Directions In Pg‐based Therapymentioning
confidence: 99%